PENGARUH POLA KERJA DAN KECERDASAN EMOSIONAL TERHADAP BUDAYA ORGANISASI KARYAWAN (STUDI KASUS PADA STIKOM CKI JAKARTA) - Atik Budi Paryanti (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTAtik Budi Paryanti, Suryadarma University, November 2013, Influence Pattern Against EmotionalIntelligence Work and Organizational Culture, (Case study In STIKOM CKI Jakarta).The purpose of this study was to determine the influence of work pattern and emotional intelligence onorganization culture at STIKOM CKI JAKARTA. The influence of emotional intelligence as an element of humanresources within an organization need to be reviewed and developed. Good working attitude needed to improveorganizational performance. A very significant in improving the performance of the organization to face thechallenges of global competition is through work pattern and emotional intelligence, the end goal is to makecontinuous improvements in order to focus on customer pattern. With the above background, the researcher isinterested in doing research on human resources in STIKOM CKI JAKARTA, it is known that the organization hasimplemented government management standards. There are three variables studied influence, namely: 1) workpattern (X1), 2) emotional intelligence (X2), to 3) the organization culture (Y).The method used in this study is a survey method with causal approach. Meanwhile, to analyze data aboutwhether or not the effect of one variable with another variable using path analysis (path analysis). Samplecollection technique is to use the technique of